국내 및 해외 단기 영어 프로그램 참가자의 영어 능숙도와 언어학습 신념 변화 - 윤정용 (The Graduate School, Ajou University, 2024)
외국어 학습자는 언어학습에 대한 나름의 신념을 가지고 있다. 신념에 따라 학습자의 행동과 학습성과가 달라질 수 있어 언어학습 신념은 L2 학습자의 개인차를 설명하는 요인 중 하나로 간 주된다. 과거에는 언어학습 신념을 안정된 요인으로 보았으나 최근에는 변화될 수 있는 역동적 요인으로 인식한다. 언어학습 신념의 특성을 고려해 보면, 학습자의 신념 변화도 학습성과와 관 계가 있을 것이다. 그러나 언어학습 신념을 주제로 한 다양한 연구에도 불구하고, 신념의 변화를 다룬 연구가 많지 않고, 특히 신념 변화와 능숙도 변화 간의 관계에 대해서는 거의 알려진 바가 없다. 이에 본 연구는 국내 및 해외 단기 영어 프로그램에 참가한 한국인 대학생을 대상으로 영 어 능숙도와 언어학습 신념의 변화를 살펴보고, 연구 결과를 바탕으로 효과적인 단기 영어 프로 그램의 설계와 학습자 지도를 위한 시사점을 도출하는 것을 목적으로 한다. _x000D_ 본 연구는 언어학습 신념 선행연구에서 제안된 혼합연구 방식을 택했다. 연구대상자는 국내 및 해외에서 각각 4주간 진행된 단기 영어 프로그램 참가자 61명으로, 토익 중심의 국내연수 프 로그램에 41명, 통합 영어학습 중심의 해외연수 프로그램에 20명이 포함되었다. 영어 능숙도의 변화를 알아보기 위하여, 사전 및 사후 모의토익을 실시하고 t-검정과 공분산분석을 통해 집단내 및 집단간 차이분석을 실시하였다. 언어학습 신념의 변화 분석에서는 프로그램과 토익점수의 상 승 정도에 따라 집단을 나누어 비교 분석하였다. Horwitz(1988)의 Beliefs about Language Learning Inventory(BALLI)를 이용해 사전 및 사후 설문조사를 실시하고, 빈도분석 및 기술통계와 더불어 Mann-Whitney U 검정과 Wilcoxon Signed-Rank 검정을 이용한 차이분석을 실시하였다. 아울러, 언어학습 신념 변화의 맥락을 이해하기 위하여 NVivo를 이용해 프로그램 기간 중 학습 자들이 작성한 학습일기를 질적으로 분석하였다. _x000D_ 영어 능숙도 변화를 분석한 결과, 국내연수와 해외연수 집단 모두 통계적으로 유의미하게 토익점수가 상승했으나 국내연수 집단에서 더 많이 점수가 올랐다. 영어 수준별로는 두 집단 모두 초급단계의 학생들이 더 큰 점수 상승을 보여, 토익을 기준으로 한 능숙도 향상에 있어 단기 영 어 프로그램이 초급 수준의 학습자에게 더 유리한 것으로 나타났다. 또한, 국내연수 집단은 듣기 와 읽기가 고르게 향상되었지만, 해외연수 집단은 듣기의 향상도가 더 커 학습환경과 교육과정 에 따라 영역별 성과는 서로 다를 수 있음이 확인되었다. 언어학습 신념의 변화를 분석한 결과, 한 달간의 프로그램을 통해서도 학습자의 신념은 일부 변화되었으며, 학습환경과 교육과정, 학습 경험 등에 따라 신념의 변화에는 차이가 있었다. 국내연수 집단은 주로 토익의 듣기와 읽기에 관한 어려움이나 자신감에 대한 신념의 변화가 있었고, 해외연수 집단은 주로 대화 관련 듣기와 말하기의 어려움과 자신감에 대한 신념의 변화가 나타났다. 어려움을 느끼는 학습자도 자신감이 커지거나 능숙도가 향상되었는데, 학습자가 느끼는 어려움은 학습전략의 수립이나 학습동기를 형성하는 계기가 되었다. 또한 능숙도의 변화 정도와는 무관하게 외국어 적성이 있다는 신념이 강해져 학습자가 생각하는 적성과 실제 적성 간에는 간격이 있음을 알 수 있었다. 해외연수 집 단은 영어권의 문화를 알아야 한다는 신념은 약해지고 문법이 중요하다는 신념이 커졌는데, 현 지 사회와의 깊이 있는 상호작용이 부족한 경우 목표언어 문화 이해를 덜 중요하게 생각하고 수 업에서 주로 다루어지는 영역이나 활동을 언어학습의 본질로 인식하였다. 학습과 의사소통 전략 에 대한 신념은 특히 변화가 컸는데, 국내연수 집단은 듣기와 읽기 전략, 해외연수 집단은 영어 대화 전략이 주된 관심사였다. 영어 사용의 적극성이나 자신감에 있어 모든 집단에서 긍정적인 변화가 발견되었는데 특히 능숙도의 향상이 큰 집단에서 신념의 변화가 컸다. 끝으로 모든 집단 의 동기가 상당히 컸는데, 통합적 동기는 대체로 유지되었으나 도구적 동기는 약해졌다. 특히 국 내연수 집단과 능숙도의 향상이 큰 집단에서 도구적 동기의 감소가 컸다. _x000D_ 본 연구를 통해 언어학습 신념은 한 달이라는 짧은 기간에도 변화될 수 있는 역동적 요인이 며, 학습환경이나 교육과정, 학습자의 경험 등에 따라 신념의 변화가 달라짐을 알 수 있었다. 본 연구는 그간 언어학습 신념 연구에서 공백으로 남아있던 단기 프로그램에서의 신념 변화와 학습 환경 및 영어 능숙도 향상 정도에 따른 신념 변화의 차이를 확인함으로써, 언어학습 신념에 대 한 이해를 확장하는 데 의의가 있다.|Foreign language learners hold their own language learning beliefs. Since learners' behavior and learning outcomes may vary depending on their beliefs, language learning beliefs are considered one of the factors explaining individual differences in L2 learners. Language learning beliefs were previously considered stable, but recently they are recognized as a dynamic factor that can change. Given the nature of language learning beliefs, changes in learners' beliefs may also be related to learning outcomes. However, despite various studies on language learning beliefs, there has been very limited number of studies on changes in beliefs, and in particular, little is known about the relationship between changes in beliefs and changes in English proficiency. Against this backdrop, this study aims to investigate changes in learners' English proficiency and beliefs about language learning through EFL and ESL short-term programs. Based on the findings, this study provides theoretical and pedagogical implications, and makes suggestions for the development of effective short-term English programs. _x000D_ This study chose mixed methods research suggested by several previous studies on language learning beliefs. The subjects were 61 Korean university students who participated in a 4-week program held at home and abroad, respectively, including 41 in the EFL TOEIC program and 20 in the ESL integrated English learning program. To examine changes in English proficiency, pre- and post-TOEIC tests were given, and t-tests and analysis of covariance (ANCOVA) were conducted. For the analysis of changes in language learning beliefs, groups were divided and compared according to the learning environment and the degree of increase in TOEIC scores. The Beliefs about Language Learning Inventory (BALLI) developed by Horwitz (1988) was administered before and after the program, and Mann-Whitney U test and Wilcoxon Signed-Rank test, along with frequency analysis and descriptive statistics, were carried out. In addition, in order to understand the context of changes in learner beliefs, NVivo was used for content analysis of the learning diaries written by the program participants during the program._x000D_ As a result of analyzing changes in English proficiency, both the EFL and ESL groups showed a statistically significant increase in TOEIC scores, but the EFL group had a greater change. In both groups, students at the beginner level showed a greater increase in scores, implying that short-term English programs are more advantageous for beginner-level learners in improving proficiency based on TOEIC. Meanwhile, the EFL group improved evenly in LC and RC, but the ESL group showed more improvement in LC, suggesting that outcomes may vary depending on the learning environment and context. As a result of analyzing changes in language learning beliefs, some changes in learners' beliefs were found even through a one-month program, and there were differences in changes in beliefs depending on the learning environment, curriculum, and learning experience. The EFL group mainly showed changes in beliefs about difficulties or confidence in listening and reading of TOEIC study, while the ESL group mainly showed changes in beliefs about difficulties or confidence in listening and speaking of English conversation. Even those who felt difficulties showed greater confidence or improved proficiency, and the difficulties learners felt served as an opportunity to develop learning strategies and form learning motivation. In addition, regardless of changes in proficiency, the belief of possessing a foreign language aptitude became stronger, showing that there is a gap between the aptitude the learner thinks and his or her actual aptitude. The ESL group's belief regarding the need to know the target culture weakened and their belief in the importance of grammar grew. In the absence of close interaction with the locals, learners placed less importance on understanding the L2 culture, and more importance on areas mainly dealt in the class. Beliefs about learning and communication strategies showed particularly large changes, with the EFL group focusing on listening and reading strategies, and the ESL group focusing on conversation strategies. Positive changes were found in all groups in terms of confidence in using English, but particularly large changes were seen in the group with greater improvement in proficiency. Lastly, all groups had high motivation for learning English, but the instrumental motivation was weakened while the integrative motivation remained unchanged. In particular, the decrease in instrumental motivation was significant in the EFL group and the group with greater improvement in proficiency. _x000D_ This study found that language learning beliefs are dynamic factors that can change even in a short period of one month, and changes in beliefs vary depending on the learning environment, curriculum, and learner's experience. This study is significant in that it expands the understanding of language learning beliefs by investigating changes in beliefs through short-term programs and by examining differences in changes in beliefs according to the learning environment and the degree of improvement in English proficiency, which have not been addressed by previous studies.
학위논문(박사)--교육학과,2024. 2
Keywords: 단기 영어 프로그램; 언어학습 신념; 영어 능숙도; 혼합연구